Linguocultural Analysis of the Most Common Greetings in the Russian, Tatar and Chinese Languages - Ramilyevna Bikmullina, Elvira; Rifkatovich Zamaletdinov, Radif (International Journal of Criminology and Sociology, 2022)
The article deals with greetings – as one of the speech genres, functioning in every language. Despite the universality of this speech genre, there are differences and peculiarities of its forms for various cultures. Of the great amount of greeting formulas functioning in the Russian, Tatar and Chinese languages the authors chose the most common three types. The formal-constructive, communicative-pragmatic and semantic characteristics are taken into consideration for a comparative analysis of the chosen units. The authors also attempted at providing a culturological interpretation of them. There are, on the one hand, greetings that are very similar in meanings among the linguocultures presented; on the other hand, there are nationally specific forms, which reflect the originality of the native speakers, their cultural traditions and axiological orientations. The study of greetings can give a key to understanding the nations’ worldview structure, the traits of mentality, as well as be a basis for successful relationships in cross-culture communication.